2019
DOI: 10.1007/978-3-030-28151-9_5
|View full text |Cite
|
Sign up to set email alerts
|

The Structures of Eukaryotic Transcription Pre-initiation Complexes and Their Functional Implications

Abstract: Transcription is a highly regulated process that supplies living cells with coding and non-coding RNA molecules. Failure to properly regulate transcription is associated with human pathologies, including cancers. RNA polymerase II is the enzyme complex that synthesizes messenger RNAs that are then translated into proteins. In spite of its complexity, RNA polymerase requires a plethora of general transcription factors to be recruited to the transcription start site as part of a large transcription pre-initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 286 publications
(611 reference statements)
1
37
0
2
Order By: Relevance
“…A sophisticated network of protein-protein and protein-nucleic acid interactions is established, producing conformational and activity changes in RNAPII through the transcription cycle. Thus, a pre-initiation complex (PIC), composed basically of general transcription factors (GTFs: TFIIA, B, D, E, F, and H), Mediator and RNAPII, is assembled at the gene promoters, opening the DNA to initiate transcription (Greber and Nogales, 2019;Schier and Taatjes, 2020). Other factors acting as activators/co-activators and repressors/co-repressors can modulate the transcription activity (Ho and Shuman, 1999;Thomas and Chiang, 2006;Hahn and Young, 2011;Roeder, 2019).…”
Section: Rnapii Phosphorylationmentioning
confidence: 99%
See 3 more Smart Citations
“…A sophisticated network of protein-protein and protein-nucleic acid interactions is established, producing conformational and activity changes in RNAPII through the transcription cycle. Thus, a pre-initiation complex (PIC), composed basically of general transcription factors (GTFs: TFIIA, B, D, E, F, and H), Mediator and RNAPII, is assembled at the gene promoters, opening the DNA to initiate transcription (Greber and Nogales, 2019;Schier and Taatjes, 2020). Other factors acting as activators/co-activators and repressors/co-repressors can modulate the transcription activity (Ho and Shuman, 1999;Thomas and Chiang, 2006;Hahn and Young, 2011;Roeder, 2019).…”
Section: Rnapii Phosphorylationmentioning
confidence: 99%
“…Functional and structural studies with S. cerevisiae have provided the majority of the existing knowledge about RNAPII transcription mechanisms, regulation and coordination with other cellular processes (Cramer, 2019a;Cramer, 2019b;Roeder, 2019). Recent structural data combined with functional studies have advanced our understanding of RNAPII transcription in general and that of PIC function, structure and dynamics in particular (Greber and Nogales, 2019;Schier and Taatjes, 2020). Resolution of the RNAPII structure by X-ray crystallography about 20 years ago showed that its twelve subunits are folded and assembled into four mobile modules: the core module, formed by the active center (Rpb1 and Rpb2) and assembly platform (Rpb3, Rpb10, Rpb11, and Rpb12); the jaw-lobe module, made up of Rpb1 and Rpb9; the shelf module containing the foot and cleft domains of Rpb1 and the lower jaw and assembly domains of Rpb5; and the stalk module, formed by Rpb4 and Rpb7, which in the case of S. cerevisiae can be dissociated from the 10-subunit core polymerase (Cramer et al, 2000;Cramer et al, 2001;Gnatt et al, 2001;Armache et al, 2003;Bushnell and Kornberg, 2003).…”
Section: Rnapii Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations
“…This PIC is a large protein biopolymer with a molecular weight of about 3 M Da [ 1 ]. During the last decade, the X-ray crystallographic structures of several PICs containing different arrangement of RNAPII, TFIIs (GTFs) and coactivators have been solved and they are reviewed in reference [ 9 ].…”
Section: Proteins and Core Dna Promoter Elements Involved In The Tmentioning
confidence: 99%